Perceived Self-Efficacy of Postgraduate Students - صالح زينة علي; حسن فؤاد كاظم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research aims to identify the perceived self-efficacy of postgraduate students. The research sample was determined from (400) male and female postgraduate students (Masters - Doctorate) at Al-Qadisiyah University. They were selected using a stratified random method with proportional distribution. Regarding the research tool, the researcher built a tool to measure the self-efficacy variable based on the theory of (Bandura: 1997). The scale consisted of (36) paragraphs after extracting the psychometric properties. The researcher adopted the descriptive approach. The researcher concluded that the research sample enjoys perceived self-efficacy. Based on what the study results showed, the researcher presented a set of recommendations and suggestions.